2021
DOI: 10.3390/w13081018
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Constructed Floodplain Ponds into Nature-Like Fish Passes Supports Fish Diversity in a Heavily Modified Water Body

Abstract: Fish passes facilitate fish movement in fragmented river systems, yet they can also provide important habitat functions. This study investigated the fish community composition of different constructed habitat types (fluvial habitats, floodplain ponds) within fish passes in relation to habitat characteristics in order to deduce recommendations for fish-friendly designs of such structures. Fish community structures within passes differed significantly from those in the main river, comprising a high number of rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In RR, the changes in habitat quality and space were different as 2 years after restoration, only scarce bank vegetation was present compared to the other habitats. Due to the higher water level in summer, the constructed small side‐channels in RR were completely flooded, providing additional aquatic habitats resembling small branches of the former braided river (Pander et al, 2021) as indicated for variation 1 of this habitat type. Braided, anabranching river courses are nowadays scarce in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RR, the changes in habitat quality and space were different as 2 years after restoration, only scarce bank vegetation was present compared to the other habitats. Due to the higher water level in summer, the constructed small side‐channels in RR were completely flooded, providing additional aquatic habitats resembling small branches of the former braided river (Pander et al, 2021) as indicated for variation 1 of this habitat type. Braided, anabranching river courses are nowadays scarce in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted at the River Inn, a formerly braided river (http://www.geoportal.bayern.de/bayernatlas, Pander et al, 2021). Nowadays, this river comprises a straightened single channel intensively used for hydropower generation (run‐of‐river power plants) with embankments for flood protection.…”
Section: Methodsmentioning
confidence: 99%
“…The high density and diversity of aquatic insect larvae can make an important contribution to the food web of nature‐like bypass systems, as previous studies have shown that these restoration measures in the River Inn are also used by highly endangered fish species such as the European grayling, which has suffered from severe declines throughout the area (Mueller, Pander, & Geist, 2018). Observations revealed that this species uses nature‐like bypass systems as spawning habitat in spring (Nagel et al, 2021), but also as foraging habitat throughout the year, as it was documented in the bypass in comparatively high densities year‐round (Pander, Nagel, & Geist, 2021). The European grayling is a typical drift feeding species, preying on macroinvertebrates drifting in the water column (Hellawell, 1971).…”
Section: Discussionmentioning
confidence: 98%
“…The fish community of this river was formerly dominated by drift feeding salmonids such as grayling and brown trout as well as several rheophilic cyprinid species. To date these species still exist, but the community has shifted toward less specialized and ubiquitous species (Pander, Nagel, & Geist, 2021; Pander, Nagel, Ingermann, & Geist, 2021). Anthropogenic alteration, particularly bank stabilization and hydropower installation, changed the former river course dramatically to a widely dammed and uniform waterbody (Pander, Nagel, & Geist, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation